Impact of anticoagulation on upper‐gastrointestinal bleeding in cirrhosis. A retrospective multicenter study. Issue 2 (27th April 2015) - Cerini, Federica; Gonzalez, Javier Martínez; Torres, Ferran; Puente, Ángela; Casas, Meritxell; Vinaixa, Carmen; Berenguer, Marina; Ardevol, Alba; Augustin, Salvador; Llop, Elba; Senosiaín, Maria; Villanueva, Càndid; et al.
<x xml:space="preserve">Abstract</x> Recent studies have shown that liver cirrhosis (LC) behaves as an acquired hypercoagulable state with increased thrombotic risk. This is why anticoagulation therapy (AT) is now frequently used in these patients. Variceal bleeding is a severe complication of LC. It is unknown whether AT may impact the outcome of bleeding in these patients. Fifty‐two patients on AT with upper gastrointestinal bleeding (UGIB) were evaluated. Portal vein thrombosis (PVT) and different cardiovascular disorders (CVDs) were the indication for AT in 14 and 38 patients, respectively. Overall, 104 patients with LC and UGIB not under AT matched for severity of LC, age, sex, source of bleeding, and Sequential Organ Failure Assessment (SOFA) score served as controls. UGIB was attributed to portal hypertension (PH) in 99 (63%) patients and peptic/vascular lesions in 57 (37%). Twenty‐six (17%) patients experienced 5‐day failure; SOFA, source of UGIB, and PVT, but not AT, were independent predictors of 5‐day failure. In addition, independent predictors of 6‐week mortality, which was observed in 26 (11%) patients, were SOFA, Charlson Comorbidity index, and use of AT for a CVD. There were no differences between patients with/without AT in needs for rescue therapies, intensive care unit admission, transfusions, and hospital stay. Conclusions: Factors that impact the outcome of UGIB in patients under AT are degree of multiorgan failure and comorbidity, but not AT itself. (Hepatology 2015;62:575–583